Women, Gender equality and COVID-19 - Carli, Linda L (Gender in management, 2020)
Purpose This paper aims to review the existing literature on the effects of the COVID-19 pandemic on gender and work roles to determine whether the pandemic has undermined the status, pay and advancement of women or has provided opportunities for reducing gender inequality. Design/methodology/approach The author reviewed the literature on the effects of COVID-19 and past pandemics on gender equality, focusing on job loss, the effects of being in essential occupations on health and well-being, the increased domestic responsibilities of women and men due to closure of schools and other social services and the effects of telecommuting on gender roles. Findings The pandemic has generally created challenges for women’s advancement. More women than men have lost their jobs; more women than men are in essential jobs that expose them to infection and psychological stress, and women have had more work disruption than men have had because of increases in childcare and other responsibilities. On the other hand, telecommuting has increased men’s amount of childcare, and this does have the potential to increase men’s childcare responsibilities in the long term, thereby reducing the gender gap in domestic responsibilities and increasing gender equality. Research limitations/implications The COVID-19 pandemic is still ongoing and the research on the pandemic’s effects are new and ongoing. Originality/value To the best of the author’s knowledge, this is the first scholarly review of the literature on the potential effects of COVID-19 on the gender gap in pay and advancement.